Pulmonary Manifestations of Polymyositis/Dermatomyositis - Hallowell, Robert W.; Ascherman, Dana P.; Danoff, Sonye K. (Seminars in Respiratory and Critical Care Medicine, 2014)
The idiopathic inflammatory myopathies are a group of connective tissue diseases marked by varying degrees of muscle inflammation and clinical involvement of multiple organs, most notably, the lung. Pulmonary manifestations consist primarily of interstitial lung disease (ILD), which is associated with significant morbidity and mortality in myositis patients. Several myositis-specific antibodies have been discovered, as well as antibodies targeting various aminoacyl-tRNA synthetase enzymes. These antibodies are associated with various clinical features and a risk for developing ILD, and their presence carries a prognostic value in myositis patients. Steroids remain the first-line treatment for myositis-associated ILD and the antisynthetase syndrome, though other traditional immunosuppressants have demonstrated efficacy in numerous studies. While a majority of patients experience either stabilization or improvement in lung imaging and function, fatal progression is still reported in a significant number of cases. Further research is needed to develop more effective and targeted therapies.
Keywords: idiopathic inflammatory myopathies; polymyositis; dermatomyositis; interstitial lung disease; nonspecific interstitial pneumonia; myositis-specific autoantibodies